Exploring the Role of Crisis Intervention Teams in Mental Health Services - Wei, Qin (Eximia, 2021)
This paper discusses the role of the police force in mental health service provision, analyzes the effectiveness of the Crisis Intervention Teams (CIT) utilizing the Toronto police service as an example, explores the application of CIT from a service user perspective, and concludes by proposing an innovative strategy to improve the performance of the CITs. This paper argues that although the CIT is a powerful responder for mental health crises, it may not be the best choice for clients.